2019
DOI: 10.1111/cob.12312
|View full text |Cite
|
Sign up to set email alerts
|

Obesity prevention in corticosteroid‐treated patients: Use and effectiveness of strategies for weight management

Abstract: Summary We conducted a systematic review to identify the use and effectiveness of clinical interventions to prevent or mitigate weight gain in patients using systemic corticosteroids. We independently searched nine bibliometric databases for reviews and longitudinal studies published up to 26 October 2018, and assessed the quality of studies meeting inclusion criteria. We identified 3893 records and screened 3037 eligible studies, read four full‐texts and extracted data from three randomized control trials. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Therefore, we suggest that further studies on this topic should define reference weight as the weight months before glucocorticoid initiation rather than the weight at glucocorticoid initiation. Third, our study identified at-risk patients who should be particularly targeted for weight gain prevention (e.g., dietary habits, increased physical exercise), even though the best prevention of weight gain is unknown to date (28).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggest that further studies on this topic should define reference weight as the weight months before glucocorticoid initiation rather than the weight at glucocorticoid initiation. Third, our study identified at-risk patients who should be particularly targeted for weight gain prevention (e.g., dietary habits, increased physical exercise), even though the best prevention of weight gain is unknown to date (28).…”
Section: Discussionmentioning
confidence: 99%
“…Derived from cortisones, this class of drugs exerts its influence by downregulating the expression of numerous genes through interactions with their transcription factors [160,161]. However, prolonged use of corticosteroids is associated with significant side effects, including weight gain, swelling, hypertension, diabetes, and increased susceptibility to infections [162][163][164][165]. The literature contains poor data about the enteral use of such a class of molecules in OA contexts.…”
Section: Steroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…A recent meta-analysis identified only 2 studies regarding obesity prevention in pediatric patients receiving corticosteroids during treatment of acute lymphoblastic leukemia, but they found that diet combined with exercise leads to less of an increase in body mass index (BMI) z-scores. 20 This underscores the importance of diet education to encourage an overall healthy diet and lowcalorie alternatives for snacks. 9 If patients experience weight gain, psychosocial support regarding perception of body image may be beneficial, especially in adolescents.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Data regarding dietary management of corticosteroid‐induced weight gain in children are sparse. A recent meta‐analysis identified only 2 studies regarding obesity prevention in pediatric patients receiving corticosteroids during treatment of acute lymphoblastic leukemia, but they found that diet combined with exercise leads to less of an increase in body mass index (BMI) z ‐scores 20 . This underscores the importance of diet education to encourage an overall healthy diet and low‐calorie alternatives for snacks 9 .…”
Section: Pharmacologic Therapymentioning
confidence: 99%